A parent-friendly Android application - Cao, Yuxuan (2019)
This project focuses on the development of an Android application to help parents/student with the child’s education. This application has 3 main functions, one is to help ease parents’ burden in finding suitable tutor by linking them with tutors. Another is to provide a place for the teachers to look out for students. Last is that allowing users to share experience in the free discussion forum. Student may also post question to look out for an answer. In order to archive development of this Android application, Android Studio will be used as the main Integrated Development Environment and MySQL will be used as main database in this project.